Optimization of the design parameters of fly ash-based geopolymer using the dynamic approach of the Taguchi method. (20th September 2019) - Onoue, Kozo; Iwamoto, Takeomi; Sagawa, Yasutaka
Graphical abstract: Highlights: Dynamic approach of the Taguchi method is applied to optimize FAGP mortar. Design parameters effects on SN ratios and sensitivities are clarified. Optimized system for preparation of FAGP mortar is established. Optimized FAGP mortar has practically sufficient strength and durability. Abstract: The dynamic approach of the Taguchi method is applied to optimize the mixture proportions and manufacturing conditions of fly ash-based geopolymer (FAGP) mortar using fly ash produced at two different thermal power plants in the Kyushu region, Japan. Ground granulated blast-furnace slag (GGBS) is also used as an activation powder. The design parameters of a system, with the volume ratio of powder to alkaline activating solution as the input value and the flow value as well as the flexural and compressive strengths as the output values, are optimized based on the calculation of the signal-to-noise ratio. As a result, optimum values for the mass ratio of sodium silicate solution to sodium hydroxide solution, concentration of sodium hydroxide solution, GGBS replacement ratio, mixing time, curing temperature, and cumulative temperature in heat curing are obtained. The values of the optimized design parameters are almost the same, regardless of the type of fly ash. The compressive strength of the optimized FAGP mortar ranged from 28.8 N/mm 2 to 47.1 N/mm 2 at 2 days, corresponding to the input values. Furthermore, it is confirmed that the optimized FAGP mortar has strength stability and sulfuric acid resistance up to 91 days sufficient for practical purposes.